Use of Audio Visual Media to Increase Student Motivation and Learning Outcomes - Devy Habibi Muhammad; Anindya Putri Susanti; Danis Imamatul Chusniyah; Hanifah Nurul Shodiqoh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is an effort to increase student motivation and learning outcomes in PAI learning in class VII SMPIT Permata. The problem examined in this article is how the use of media can be applied in PAI subjects and whether the use of audio-visual media can increase student motivation and learning outcomes. The problem that arises in this research is the level of student learning achievement which is still low or has not reached the minimum completeness criteria score, namely 75. This research uses the classroom action research (PTK) method to provide a solution to this problem. The research results show that learning activities using audio-visual media provide learning motivation to students because there is an increase in student learning outcomes. The students' understanding of PAI material on average is quite good, as shown by 12 students, 11 students (92%) achieved completeness, 1 student (8%) did not achieve completeness. One of the obstacles found in using this learning media is that there are still some students who remain less active even though audio-visual media has been implemented.